Theoretical And Procedural Reference for Classroom Interaction - Field Approach - bendar, Nassima. (International Journal of Psychosocial Rehabilitation, 2022)
The upbringing is the procedure of interaction between one person and another in a specific time and place to achieve one educational purpose. Therefore, class interaction has been the eye of the education’s process . which its importance lies in its members; for it helps to improve the education’s quality, diminish the teacher’s dominance, and to offer an opportunity for the learner to exchange ideas and thoughts in order to enrich it. Hence, the success of the learning procedure depends mostly on the learner, for that purpose, our current study targeted the diagnose of the accreditation of class interaction both: theoretical and practical, amongst secondary school’s students by investigating through the means of prevailing class interaction inside the classrooms.